EVALUATING THE PRODUCTION EFFICIENCY OF TAN TRIEU POMELO IN DONG NAI PROVINCE - Vũ Thịnh Trường; Trần Đức Thuận; Võ Anh Kiệt; Nguyễn Đức Nam (HUIT Journal of Science, 2025)
The Tan Trieu pomelo, an important crop in the agriculture of Dong Nai province, mainly concentrated in Vinh Cuu district, has been the focus of many agricultural promotion policies of the province in the past decade. This study aims to measure and assess the influence of various factors on the production efficiency of Tan Trieu pomelo growers. The Data Envelopment Analysis (DEA) method and the Tobit regression model is sequentially employed to analyze data from 180 samples of farmers for the years 2021 and 2022. The research results show that the production efficiency of farmers, measured by technical efficiency, allocation efficiency, and cost efficiency, reached 0.83%; 0.63%; and 0.52% respectively. The positively significant factors affecting technical efficiency in both years are: Cultivating Experience, Technical training, Participation in Agricultural Cooperative. Conversely, “Access to credit” factor negatively affects technical efficiency in 2021. Interestingly, practicing good agricultural techniques - VietGAP does not affect the technical efficiency of farmers. The research results provide empirical evidence for local government to improve agricultural development policies in general and Tan Trieu pomelo cultivation in particular.